A Mitochondria-Penetrating Peptide Exerts Potent Anti-Plasmodium Activity and Localizes at Parasites' Mitochondria - Sangdao Somsri; Mathirut Mungthin; Natthaporn Klubthawee; Poom Adisakwattana; Warunee Hanpithakpong; Ratchaneewan Aunpad (MDPI AG, 2021)
Mitochondria are considered a novel drug target as they play a key role in energy production and programmed cell death of eukaryotic cells. The mitochondria of malaria parasites differ from those of their vertebrate hosts, contributing to the drug selectivity and the development of antimalarial drugs. (Fxr)3, a mitochondria-penetrating peptide or MPP, entered malaria-infected red cells without disrupting the membrane and subsequently killed the blood stage of P. falciparum parasites. The effects were more potent on the late stages than on the younger stages. Confocal microscopy showed that the (Fxr)3 intensely localized at the parasite mitochondria. (Fxr)3 highly affected both the lab-strain, chloroquine-resistant K1, and freshly isolated malaria parasites. (Fxr)3 (1 ng/mL to 10 μg/mL) was rarely toxic towards various mammalian cells, i.e., mouse fibroblasts (L929), human leukocytes and erythrocytes. At a thousand times higher concentration (100 μg/mL) than that of the antimalarial activity, cytotoxicity and hemolytic activity of (Fxr)3 were observed. Compared with the known antimalarial drug, atovaquone, (Fxr)3 exhibited more rapid killing activity. This is the first report on antimalarial activity of (Fxr)3, showing localization at parasites' mitochondria.